Faktor Faktor Yang Mempengaruhi Keputusan Konsumen Menggunakan Jasa Glow Wedding & Event Planner - Widiani, Komang Dewik Astiti; Kusumarini, Indah; Wirata, I Nengah (Journal of Event and Convention Management, 2025)
This study aims to analyze the factors that influence consumer decisions in using the services of Glow Wedding & Event Planner in Bali. The study used a quantitative approach with a survey method through a questionnaire distributed to 98 respondents who had used the company's services. The variables studied included price, promotion, product, and service, with purchasing decisions as the dependent variable. Data analysis techniques used included validity tests, reliability tests, and factor analysis (Confirmatory Factor Analysis/CFA). The results of the study showed that the four independent variables influenced consumer decisions, with the product as the most dominant factor influencing consumer decisions. The promotion factor was the lowest factor in influencing consumer decisions to use the services of Glow Wedding & Event Planner.